Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material and application thereof in texturing filling of sleeve surface
By filling the inner wall of the sleeve with Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material, the wear problem of traditional sleeves under high frequency use and high cyclic load conditions is solved, significantly improving wear resistance and fatigue resistance, and extending service life.
Patent Information
- Application Number
- CN202510013583.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional sleeves are prone to wear problems under high frequency use and high cycle load conditions, and existing modification methods cannot effectively improve wear resistance and fatigue resistance.
The SAC composite wear-resistant material enhanced by Ti4AlN3-Al2O3 is uniformly mixed and pressed through vacuum ball milling and cold isostatic pressing technology, and then the composite material is made by melt spray granulation technology, and textured and textured filling is performed on the inner wall of the sleeve.
It significantly improves the wear resistance and fatigue resistance of the sleeve, extends the service life, reduces the coefficient of friction, reduces energy loss, and maintains stability in harsh environments.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation and application of metal-based composite materials, and specifically relates to a Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material and its application in sleeve texturing filling. Background Art
[0002] During the relative movement of traditional machined sleeves with other parts, the surface material will gradually be lost due to friction. When hard particles from the outside enter between the sleeve and the mating parts, abrasive wear will occur. These particles may come from dust, sand or metal chips in the working environment. When the sleeve is subjected to alternating loads, fatigue cracks will occur on the surface or inside after a certain number of cycles. The custom processing cost of non-standard sleeves is high, and there are few replaceable parts on the market. The sleeve parts are required to have a long life, wear resistance on the contact surface, and stability in oxidizable and corrosive environments. Therefore, it is particularly important to improve the interface performance of friction contact through technical means.
[0003] The existing tribological modification methods for the inner wall of the sleeve mainly use mechanical grinding, polishing and other processes to reduce the surface roughness of the inner wall of the sleeve, making the surface smoother, thereby reducing the friction coefficient and reducing wear. However, single polishing and grinding cannot change the surface hardness, wear resistance and other properties. The existing technology also improves the hardness and wear resistance of the inner wall of the sleeve through chemical nickel plating, chemical copper plating and other methods, but when subjected to large external forces or in harsh environments such as humidity, the nickel plating and copper plating layers are easily separated from the substrate, resulting in coating failure. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in view of the deficiencies in the above-mentioned prior art, which can solve the wear problem of traditional sleeves under high-frequency use and high-cycle load conditions, significantly improve wear resistance, reduce surface wear, and extend the service life of the tool.
[0005] On the basis of the above, the present invention also provides an application of the above-mentioned Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material in sleeve texturing filling to solve the problem of unstable friction coefficient, and the composite wear-resistant material and texture texture can effectively disperse stress concentration points, improve the fatigue resistance of the sleeve, and delay the formation and expansion of fatigue cracks.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is: A Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material, the raw materials of which include, by mass percentage, 4-11wt.% of titanium aluminum nitrogen MAX phase ceramic, 84-94wt.% of SnAgCu alloy and 2-5wt.% of nano Al2O3. SAC represents the three metal elements Sn, Ag and Cu.
[0007] Preferably, the titanium aluminum nitrogen MAX phase ceramic, i.e., Ti4AlN3MAX phase ceramic powder, has a particle size of preferably less than 200 mesh, generally 200-500 mesh; both nano Al2O3 and SnAgCu alloy are powder raw materials, the particle size of nano Al2O3 is preferably 100-200nm, and the particle size of SnAgCu alloy is 2-12μm; the SnAgCu alloy consists of Sn 95-97%, Ag 2-4%, and Cu0.1-1% by mass.
[0008] The preparation method of the above-mentioned Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material is as follows: first, Ti4AlN3MAX phase ceramic powder 4-11wt.%, SnAgCu powder 84-94wt.% and nano Al2O3 powder 2-5 wt.% are mixed by mass percentage, and then vacuum ball milled evenly, loaded into a mold, and pressed by cold isostatic pressing to obtain a Ti4AlN3-nano Al2O3-SAC solid blank; then, the solid blank is subjected to melt spray granulation technology to be made into a Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material.
[0009] Preferably, the preparation method of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material specifically comprises the following steps: 1) According to mass percentage, 4-11wt.% of Ti4AlN3MAX phase ceramic powder, 84-94wt.% of SnAgCu powder and 2-5wt.% of nano-Al2O3 powder are mixed, and after vibrating the mixture, the mixture is put into a vacuum ball mill for ball milling to obtain Ti4AlN3-nano-Al2O3-SAC initial powder ingredients; wherein the ball milling speed is 300-500rpm, and the ball milling time is more than 3h; 2) The Ti4AlN3-nano-Al2O3-SAC initial powder ingredients are uniformly loaded into the mold, and the mold is filled tightly by vibration, stirring and other methods, and a small amount of water is added as a liquid medium, and then the cold isostatic pressing equipment is started to press and mold, and after demolding and drying, a Ti4AlN3-nano-Al2O3-SAC solid blank is obtained; wherein the cold isostatic pressing pressure is 200-300MPa, and the holding time is 10-20min; 3) Melting Ti4AlN3-nano Al2O3-SAC solid blank under vacuum to obtain a melt; atomizing the melt, and then rapidly spraying it into water to cool and solidify, forming a powdery spherical Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material on the water surface, wherein the diameter of the spherical powder is 8-40 μm; wherein the melting temperature is 220-230° C., and the atomizing gas pressure is 1-2 MPa.
[0010] The application of the above-mentioned Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material in the texturing filling of the sleeve is as follows: first, a fan-ring texture is processed on the inner wall of the sleeve by laser texturing technology, and then a phosphating treatment is performed to deposit a dense phosphate protective film in the grooves of the fan-ring texture, and then a cold spraying method is used to uniformly coat the Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material on the phosphate protective film, and then vacuum infiltration is performed to finally form a Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant coating on the inner wall of the sleeve.
[0011] Preferably, the fan-ring texture is composed of multiple rows of fan rings arranged side by side in the transverse direction, and each row of fan rings is staggered and connected with two adjacent rows of fan rings; each row of fan rings includes multiple fan ring units arranged in the longitudinal direction, and the bottom arc of any fan ring unit is on the same circumference as the top arc of the adjacent fan ring unit; the contour line of each fan ring unit is a groove, the groove depth is 0.30-0.40mm, the groove width is 2.5-3.5mm, and the groove is used for texturing filling. Furthermore, the width W of each fan ring unit is 2.5-3.5mm (preferably 3.10-3.30mm), and the spacing d between the top arc and the bottom arc is 0.35-0.43mm.
[0012] The application of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in sleeve texturing filling, the application method specifically comprises the following steps: (1) After cleaning and drying the inner wall of the sleeve, a laser engraving machine is used to process the fan-ring texture on the inner wall of the sleeve according to the geometric parameters of the fan-ring texture; wherein the power of the laser engraving machine is 20-30W, the defocus distance is 1.5-2.5mm, and the processing speed is 0.5-1.2 mm / s; (2) immersing the inner wall of the sleeve obtained in step (1) in a zinc-calcium phosphating solution for phosphating treatment to form a phosphating film; wherein the phosphating treatment time is 10-15 minutes and the temperature is 50-80° C.; (3) adding a silane coupling agent to the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material, and uniformly mixing the mixture by ultrasonic mixing to obtain a silane coupling agent-modified Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; wherein the amount of the silane coupling agent is 1.8-2.1wt.% of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; (4) The Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material modified with silane coupling agent obtained in step (3) is filled into the grooves of the fan-ring texture on the inner wall of the sleeve obtained in step (2) by cold spraying technology, and then transferred to a vacuum sintering furnace for vacuum sintering; wherein the working gas for cold spraying is helium, the working pressure is 1.5-2.5 MPa, the working gas temperature is 180-190°C, and the spray angle relative to the geometric section of the inner wall is 77-85°; the vacuum sintering temperature is 150-180°C, and the duration is 80-100 min; (5) The sleeve after vacuum sintering in step (4) is heated to 220-250°C for vacuum infiltration. After the infiltration is completed, it is slowly cooled to room temperature and then polished to obtain a sleeve with surface texture filled with Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; wherein the vacuum infiltration time is 20-40 minutes, and the slow cooling rate is controlled within 10°C / min.
[0013] In the above application method, the purposes of phosphating treatment and cold spraying are respectively to form a phosphating film in the grooves of the fan-ring texture and fill them with composite wear-resistant materials. Although the non-groove area will also form a phosphating film and cover the composite wear-resistant material to a certain extent during operation, the last step of polishing in this application method will polish the non-groove area to expose the material of the inner wall of the sleeve itself. The grooves of the fan-ring texture are filled with composite wear-resistant materials, and the height of the entire inner wall of the sleeve is flat.
[0014] Furthermore, the sleeve is fastened with a vehicle wheel hub bolt and is made of chrome-molybdenum steel, and the further preferred material is 42CrMo alloy steel.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses Ti4AlN3MAX phase and nano-Al2O3 as the reinforcing phase of the SnAgCu solid lubricating phase. The mechanism is that when the SnAgCu alloy is self-lubricating and deforming to reduce friction and wear, the Ti4AlN3 layered structure provides a high-strength support skeleton, and maintains the stability of the structure after self-lubricating supplementation when bearing a large load. A small amount of nano-Al2O3 is further evenly dispersed in the lubricating phase matrix at the nanoscale to improve the wear resistance of synergistic lubrication. The present invention ensures that the SnAgCu alloy maintains sufficient rigidity while fully exerting its lubrication and protective properties by limiting the ratio between SnAgCu, Ti4AlN3 and nano. If the reinforcing phase content is too high, it will cause agglomeration, fully hindering the movement of dislocations, and the SnAgCu self-lubricating film will be uneven or even fractured. If the reinforcing phase content is too low, the mechanical strength and interphase structural stability will not be significantly affected, and the overall strength will not be significantly improved. SnAgCu is easily deformed and consumed during friction contact. From the perspective of traditional material manufacturing, the chemical properties of metals and ceramics are quite different and it is not easy to form stable chemical bonds. However, in the SnAgCu interface lubrication migration of the present invention, ceramic Ti4AlN3 and nano-Al2O3 have a microscopic interface regulation effect, while maintaining the chemical properties of each component itself. The self-lubricating effect of the corresponding working conditions and life requirements is adapted by adjusting the content of Ti4AlN3, and the overall wear resistance is controlled by adjusting the nano-Al2O3.
[0016] The new Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material provided by the present invention exhibits significant comprehensive tribological properties. In terms of wear resistance, it has been significantly improved compared to traditional sleeve materials. The new composite wear-resistant material can effectively resist the wear caused by long-term friction between the sleeve and the hub bolt, greatly extending the service life of the sleeve, and reducing problems such as reduced accuracy and functional failure caused by wear. Moreover, the new Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material described in the present invention has good oxidation resistance and corrosion resistance, and can maintain stability in oxidation reactions generated by various media contacts and in humid environments, ensuring the structural integrity and performance reliability of the sleeve. At the same time, the self-lubricating effect of the SAC composite wear-resistant material reduces the friction coefficient, which not only reduces energy loss, but also further reduces wear.
[0017] (2) The present invention innovatively adopts cold isostatic pressing combined with melt spray granulation technology to prepare SAC composite wear-resistant materials, which solves the problem of uniform distribution and internal bonding of different phases of metal and ceramic materials, while ensuring manufacturing efficiency and quality. The fine particles of SAC alloy phase and reinforcement phase formed by spray granulation form a tightly bound and evenly distributed structure inside, which is conducive to improving the comprehensive performance of the material, effectively improving the micro-scale mechanical bonding between Ti4AlN3-Al2O3 reinforcement phase and SnAgCu solid lubrication phase, improving the wear resistance and life of the material, and at the same time, the distribution of each phase in the material is uniform.
[0018] (3) The Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material of the present invention is filled in the texture of the inner wall of the sleeve. It has strong adaptability during use and can automatically release lubricating substances during friction, thereby reducing the friction coefficient and spontaneously forming a lubricating film. Ti4AlN3-Al2O3 and SAC synergistically enhance the lubrication and wear protection effect of the sleeve under dynamic load. This adaptive function enables the sleeve to maintain stable performance under high cycle load and high friction conditions, reduce wear and loss, and ensure long-term reliable use. This application performs tribological modification on the contact interface of non-standard manufacturing sleeves, reducing the problem of overall replacement of parts due to partial failure under fatigue, easy oxidation and corrosive environment. Compared with chromium-molybdenum steel, the SAC composite wear-resistant material of the present invention has toughness on the interface, which can avoid failure caused by excessive brittleness under complex stress conditions. The SAC composite wear-resistant material of the present invention is filled in the inner wall surface of the textured sleeve, which can better cooperate with the matrix to jointly withstand external forces and wear.
[0019] (4) When the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material of the present invention is applied to the texture filling of the inner wall of the sleeve, cold spraying technology and vacuum sintering process are used to ensure that the composite wear-resistant material is evenly distributed on the inner wall of the sleeve; and the silane coupling agent used in advance improves the interface bonding ability between the material and the sleeve matrix, and the surface phosphate crystals are formed by phosphating treatment, which synergistically improves the adhesion of the material, ensures the firmness of the material after the texture filling on the sleeve surface, and makes it difficult to fall off, so as to continuously exert its excellent performance. These measures make the texture filling dense and uniform, ensure the high bonding strength and uniform and reliable protection performance maintained under different working conditions, and further reduce the friction and wear of the inner wall of the sleeve.
[0020] (5) In the present invention, the inner wall of the sleeve adopts a fan-ring texture, which effectively improves the binding force and adhesion of the filling area through mechanical meshing, and at the same time increases the lubrication storage capacity and wear debris collection capacity on the contact surface of the inner wall of the sleeve when in use. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The invention discloses a preparation process of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material and an application process thereof in a 42CrMo alloy steel sleeve.
[0022] Figure 2 The present invention discloses a structural diagram of a 42CrMo alloy steel sleeve and a textured surface of its inner wall using the Ti4AlN3-Al2O3-reinforced SAC composite wear-resistant material of the present invention.
[0023] Figure 3 This is a microscopic characteristic picture of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared by the present invention.
[0024] Figure 4 This is a microscopic morphology photograph of a wear tail section of the wear mark after the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in Example 1 of the present invention is applied to a 42CrMo alloy steel sleeve and a high cycle friction test is performed on the inner wall of the sleeve.
[0025] Figure 5 This is a microscopic morphology photograph of a middle section of the wear mark after the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in Example 1 of the present invention is applied to a 42CrMo alloy steel sleeve and a high cycle friction test is performed on the inner wall of the sleeve.
[0026] Figure 6 This is a microscopic morphology photograph of the wear marks after the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in Example 2 of the present invention is applied to a 42CrMo alloy steel sleeve and a friction test is performed on the inner wall of the sleeve. DETAILED DESCRIPTION
[0027] In order to better understand the present invention, the content of the present invention is clearly and completely described below in conjunction with embodiments, but the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0028] In the following embodiments, the Ti4AlN3MAX phase ceramic powder is 200-400 mesh; the particle size of the nano Al2O3 powder is 100-200nm, and the particle size of the SnAgCu alloy is 2-12μm; the SnAgCu alloy consists of Sn 95-97%, Ag 2-4%, and Cu 0.1-1% by mass.
[0029] In the following embodiments, each liter of zinc-calcium phosphating solution is composed of the following materials by weight: 96-98 g of zinc dihydrogen phosphate, 25-26 g of calcium nitrate, 8-10 g of phosphoric acid, 2.5-3 g of sodium nitrite, 7-8 g of sodium molybdate, 6.5-7 g of nickel nitrate, and the remaining components are water. The pH value is controlled at 2-3 by adjusting the content of phosphoric acid.
[0030] Example 1 A Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material, the preparation method of which specifically comprises the following steps: 1) Ti4AlN3MAX phase powder, SnAgCu powder and nano-Al2O3 powder were mixed in the weight ratio of 10wt.%, 88wt.% and 2wt.%, respectively, and the mixture was first vibrated for 40min at a vibration frequency of 35Hz, and then put into a vacuum ball mill for ball milling at room temperature 25℃, 10 -5 Torr and 500 rpm for 3 h to obtain a uniform initial powder batch; 2) The initial powder batch obtained in step 1) is uniformly loaded into the mold, and the powder is tightly filled by vibration, stirring and other methods, and deionized water is added as a liquid medium (the mass of the liquid medium is 2-3% of the initial powder batch), and the cold isostatic pressing equipment is started, the pressure is controlled to be 250MPa, and the pressure is maintained for 15 minutes, and then the pressure is slowly released and the mold is demolded and dried to obtain a Ti4AlN3-nano-Al2O3-SAC solid blank; 3) The Ti4AlN3-nano-Al2O3-SAC solid blank is melted in a vacuum atmosphere at a temperature of 230°C to obtain a composite melt; the composite solution is continuously impacted by argon gas sprayed from the equipment nozzle, and the atomizing gas pressure is 2MPa. The composite melt is crushed into mist droplets and rapidly sprayed into deionized water for cooling and solidification, forming a solid spherical powder with a diameter of 8-40μm on the water surface, i.e., Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material.
[0031] like Figure 3 As shown, the microstructure of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material is spherical with a diameter between 8 and 40 microns.
[0032] The application of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in sleeve texturing filling, the application method specifically comprises the following steps: (1) The inner wall of a 42CrMo alloy steel sleeve is ultrasonically cleaned and dried, and the inner wall of the 42CrMo sleeve is repeatedly scanned multiple times using laser engraving technology to form the desired fan-ring texture. The entire inner wall is then micro-polished on a polishing machine, and cleaned in an ultrasonic cleaning machine with anhydrous ethanol for more than 15 min and dried. The power of the laser engraving machine is 30 W, the defocus distance is 2 mm, and the processing speed is 1 mm / s. The fan-ring texture is composed of a plurality of rows of fan rings arranged side by side in the transverse direction, and each row of fan rings is staggered and connected with the two adjacent rows of fan rings. Each row of fan rings includes a plurality of fan ring units arranged in the longitudinal direction, and the bottom arc of any fan ring unit is on the same circumference as the top arc of the adjacent fan ring unit. The contour line of each fan ring unit is a groove, the groove depth is 0.30 mm, the groove width is 2.82 mm, and the groove is used for texturing filling. The width W of each fan ring unit is 3.18 mm, and the distance d between the top arc and the bottom arc is 0.41 mm.
[0033] (2) Phosphating treatment: the sleeve obtained in step (1) is immersed in a zinc-calcium phosphating solution for phosphating treatment. The treatment time is 10 min and the temperature is 60° C., and a phosphating film is formed on the inner wall of the sleeve and in its fan-shaped ring texture. The sleeve and its inner wall are then dried using a hot air drying device. The drying temperature is set at 80° C. and the drying time is 10 minutes.
[0034] (3) Add silane coupling agent KH560 to the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in this example, mix them evenly by ultrasonic mixing, set the ultrasonic frequency to 40 kHz, the temperature to 25°C, and the ultrasonic time to 1 h, to obtain a silane coupling agent-modified Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; wherein the amount of silane coupling agent used is 1.8wt.% of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material.
[0035] (4) The Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material modified with silane coupling agent obtained in step (3) is filled into the grooves of the fan-ring texture on the inner wall of the sleeve by cold spraying technology; wherein, when the cold spraying equipment is started for spraying operation, the spray gun is kept moving smoothly to ensure that the sprayed powder material can be evenly coated in the grooves of the fan-ring texture, the working gas for cold spraying is helium, the working pressure is 2.0 MPa, the working gas temperature is 185°C, and the spray angle relative to the geometric section of the inner wall is 80°; by spraying multiple times, the thickness of the coating layer is gradually increased to ensure that the formed coating layer is uniform, dense and free of pores, and completely fills the grooves of the fan-ring texture on the inner wall of the sleeve; the vacuum sintering temperature is 150°C and the duration is 80 min; (5) Place the cold sprayed sleeve in a vacuum sintering furnace and control the vacuum degree in the furnace at 10-5 Torr, sintering at 150℃ for 90 minutes, the main purpose is to remove moisture and organic matter in the coating layer; after sintering, the sintering furnace is naturally cooled to room temperature and maintained in a vacuum state to prevent the surface of the coating layer from being contaminated or oxidized by the air during the cooling process, and then transferred to the vacuum infiltration furnace, and the sleeve is gradually heated to 240℃, and the temperature is ensured to rise evenly during the heating process. When the temperature reaches 230℃, keep the temperature constant and perform insulation treatment for 30 minutes to complete the infiltration. After the infiltration is completed, gradually reduce the temperature in the infiltration furnace and slowly cool to room temperature. The cooling rate should be controlled within 10℃ per minute to avoid thermal stress caused by a sudden drop in temperature, which may cause cracking or peeling of the coating layer.
[0036] (6) The inner wall of the sleeve obtained in step (5) is polished for 20 minutes using an alumina polishing liquid (particle size of 0.05 μm) using a polishing machine until the non-groove portion of the fan-ring texture is exposed to the material of the inner wall of the sleeve itself, the groove portion is exposed to the composite wear-resistant material, and the height of the entire inner wall of the sleeve is flat. Subsequently, it is cleaned with anhydrous ethanol and an ultrasonic oscillator for 20 minutes. After drying, a 42CrMo alloy steel sleeve with a surface texture filled with Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material is obtained.
[0037] Performance test: The sleeve prepared in this embodiment is cut into pieces and sampled, and a reciprocating dry friction test is performed on its inner wall using a multifunctional friction tester. A ball-plate grinding pair is used, the grinding ball is made of 100Cr6 steel, the cut sample is 20mm long × 10mm wide × 5mm thick, the test load is 20N, and the test temperature is 25-30 o C, reciprocating frequency: 0.5 Hz; each sample completed 3 experiments, using the average friction coefficient per minute as the experimental result, each experimental time: 60 minutes; then the electron probe microscope was used to observe the microscopic morphology of the worn surface of the sample.
[0038] According to the above performance tests and microscopic morphology observations, the average friction coefficient of the 42CrMo alloy steel sleeve filled with surface textured Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material is low, only 0.413, while the average surface friction coefficient of the ordinary 42CrMo alloy steel sleeve is 0.463.
[0039] like Figure 4 and Figure 5 As shown, when the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in Example 1 is applied to a 42CrMo alloy steel sleeve, after a friction test on the inner wall of the sleeve, the wear debris particles are uniform after damage and wear on the tail section of the wear mark surface, the middle section of the wear mark maintains a uniform microstructure, the SnAgCu interface migrates and exhibits self-lubrication, and the wear debris is embedded in the groove, making the friction surface smoother.
[0040] In addition, in the actual production line, when the 42CrMo alloy steel sleeve with surface texture filled with Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in this embodiment is used as a vehicle bolt tightening sleeve, the service life is increased by about 28%.
[0041] Example 2 A Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material, the preparation method of which specifically comprises the following steps: 1) Ti4AlN3MAX phase powder, SnAgCu powder and nano-Al2O3 powder were mixed in weight ratios of 8wt.%, 90wt.% and 2wt.%, respectively. The mixture was first vibrated for 30 min at a vibration frequency of 50 Hz, and then placed in a vacuum ball mill for ball milling at room temperature 25°C, 10 -5 Torr and 400 rpm for 4 h to obtain a uniform initial powder batch; 2) The initial powder ingredients obtained in step 1) are uniformly loaded into the mold, and the powder is tightly filled by vibration, stirring and other methods, deionized water is added as a liquid medium, and the cold isostatic pressing equipment is started, the pressure is controlled to be 220MPa, the pressure is maintained for 20min, and then the pressure is slowly released and the mold is demolded and dried to obtain a Ti4AlN3-nano-Al2O3-SAC solid blank; 3) The Ti4AlN3-nano-Al2O3-SAC solid blank is melted in a vacuum atmosphere at a temperature of 230°C to obtain a composite melt; argon gas is sprayed from the equipment nozzle to continuously impact the composite solution, and the gas pressure during atomization is 1.7 MPa. The composite melt is crushed into mist droplets and quickly sprayed into deionized water to cool and solidify, forming a solid spherical powder with a diameter of 8-40 μm on the water surface, i.e., Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material.
[0042] The application of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in sleeve texturing filling, the application method specifically comprises the following steps: (1) The inner wall of a 42CrMo alloy steel sleeve is ultrasonically cleaned and dried, and the inner wall of the 42CrMo sleeve is repeatedly scanned multiple times using laser engraving technology to form the desired fan-ring texture. The inner wall is then micro-polished on a polishing machine, and cleaned in an ultrasonic cleaning machine with anhydrous ethanol for more than 15 min and dried. The power of the laser engraving machine is 25 W, the defocus distance is 2 mm, and the processing speed is 0.5 mm / s. The fan-ring texture is composed of a plurality of rows of fan rings arranged side by side in the transverse direction, and each row of fan rings is staggered and connected with the two adjacent rows of fan rings. Each row of fan rings includes a plurality of fan ring units arranged in the longitudinal direction, and the bottom arc of any fan ring unit is on the same circumference as the top arc of the adjacent fan ring unit. The contour line of each fan ring unit is a groove, the groove depth is 0.40 mm, the groove width is 3.10 mm, and the groove is used for texturing filling. The width W of each fan ring unit is 3.20 mm, and the distance d between the top arc and the bottom arc is 0.43 mm.
[0043] (2) Phosphating treatment: The sleeve obtained in step (1) is immersed in a zinc-calcium phosphating solution for phosphating treatment. The treatment time is 15 min and the temperature is 62° C., and a phosphating film is formed on the inner wall of the sleeve and in its fan-shaped ring texture. The sleeve and its inner wall are then dried using a hot air drying device. The drying temperature is set at 80° C. and the drying time is 20 minutes.
[0044] (3) Add silane coupling agent KH560 to the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in this example, mix them evenly by ultrasonic mixing, set the ultrasonic frequency to 50 kHz, the temperature to 25°C, and the ultrasonic time to 1 h, to obtain a silane coupling agent-modified Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; wherein the amount of silane coupling agent used is 2.1wt.% of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material.
[0045] (4) The Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material modified with silane coupling agent obtained in step (3) is filled into the grooves of the fan-ring texture on the inner wall of the sleeve by cold spraying technology; wherein, when the cold spraying equipment is started for spraying operation, the spray gun is kept moving smoothly to ensure that the sprayed powder material can be evenly coated in the grooves of the fan-ring texture, the working gas for cold spraying is helium, the working pressure is 2.0 MPa, the working gas temperature is 190°C, and the spray angle relative to the geometric section of the inner wall is 85°; by multiple spraying, the thickness of the coating layer is gradually increased to ensure that the formed coating layer is uniform, dense and free of pores, and completely fills the grooves of the fan-ring texture on the inner wall of the sleeve; the vacuum sintering temperature is 175°C and the duration is 100 min; (5) Place the cold sprayed sleeve in a vacuum sintering furnace and control the vacuum degree in the furnace at 10-5 Torr, sinter at 170℃ for 90 minutes; after sintering, cool the sintering furnace naturally to room temperature and maintain a vacuum state to prevent the surface of the coating from being contaminated or oxidized by the air during the cooling process, and then transfer it to the vacuum infiltration furnace, gradually heat the sleeve to 240℃, and ensure that the temperature rises evenly during the heating process. When the temperature reaches 240℃, keep the temperature constant and perform insulation treatment for 40 minutes to complete the infiltration. After the infiltration is completed, gradually reduce the temperature in the infiltration furnace and slowly cool to room temperature. The cooling rate should be controlled within 10℃ per minute to avoid thermal stress caused by a sudden drop in temperature, which may cause cracking or peeling of the coating.
[0046] (6) The inner wall of the sleeve obtained in step (5) is polished for 30 minutes using an alumina polishing liquid (particle size of 0.05 μm) using a polishing machine until the non-groove portion of the fan-ring texture is exposed to the material of the inner wall of the sleeve itself, the groove portion of the fan-ring texture is exposed to the composite wear-resistant material, and the height of the entire inner wall of the sleeve is flat. Subsequently, it is cleaned with anhydrous ethanol and an ultrasonic oscillator for 20 minutes. After drying, a 42CrMo alloy steel sleeve with a surface texture filled with Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material is obtained.
[0047] Performance test: The sleeve prepared in this embodiment is cut into pieces and sampled, and a reciprocating dry friction test is performed on its inner wall using a multifunctional friction tester. A ball-plate grinding pair is used, the grinding ball is made of 100Cr6 steel, the cut sample is 20mm long × 10mm wide × 5mm thick, the test load is 20N, and the test temperature is 25-30 o C, reciprocating frequency: 0.5 Hz; each sample completed 3 experiments, using the average friction coefficient per minute as the experimental result, each experimental time: 60 minutes; then the electron probe microscope was used to observe the microscopic morphology of the worn surface of the sample.
[0048] According to the above performance tests and microscopic morphology observations, the average friction coefficient of the 42CrMo alloy steel sleeve with surface textured filling Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material is 0.408, and the average surface friction coefficient of the ordinary 42CrMo alloy steel sleeve is 0.463.
[0049] like Figure 6 As shown, when the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material prepared in Example 2 is applied to a 42CrMo alloy steel sleeve, after a friction test on the inner wall of the sleeve, the wear scar surface maintains a uniform and smooth microstructure, and the SnAgCu reinforced by Ti4AlN3-Al2O3 exhibits excellent self-lubricating effect and surface tribological modification.
[0050] In addition, in the actual production line, the service life of the 42CrMo alloy steel sleeve with surface texture filled with Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in this embodiment is increased by about 38% when used as a vehicle bolt tightening sleeve.
[0051] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material, characterized in that: The raw materials include, by mass percentage, 4-11 wt.% of titanium aluminum nitrogen MAX phase ceramic, 84-94 wt.% of SnAgCu alloy and 2-5 wt.% of nano Al2O3.
2. The application of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material in sleeve texturing filling according to claim 1, characterized in that: The application method is: first use laser texturing technology to process fan-ring texture on the inner wall of the sleeve, then perform phosphating treatment, so as to deposit a phosphate protective film in the groove of the fan-ring texture, and then use a cold spray method to uniformly coat the Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant material described in claim 1 on the surface of the phosphate protective film, and then perform vacuum infiltration to finally form a Ti4AlN3-Al2O3 enhanced SAC composite wear-resistant coating on the inner wall of the sleeve.
3. The application according to claim 2, characterized in that: The fan-ring texture structure is composed of multiple rows of fan rings arranged side by side in the transverse direction, and each row of fan rings is staggered and connected with the two adjacent rows of fan rings; each row of fan rings includes multiple fan ring units arranged in the longitudinal direction, and the bottom arc of any fan ring unit is on the same circumference as the top arc of the adjacent fan ring unit; the contour line of each fan ring unit is a groove, the groove depth is 0.30-0.40mm, and the groove width is 2.5-3.5mm.
4. The use according to claim 3, characterized in that: The width of each fan ring unit is 2.5-3.5mm, and the distance between the top arc and the bottom arc is 0.35-0.43mm.
5. The application according to claim 2, characterized in that: The application method specifically includes the following steps: (1) After cleaning and drying the inner wall of the sleeve, a laser engraving machine is used to process the fan-ring texture on the inner wall of the sleeve according to the geometric parameters of the fan-ring texture; (2) immersing the inner wall of the sleeve obtained in step (1) in a zinc-calcium phosphating solution for phosphating to form a phosphating film; (3) adding a silane coupling agent to the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material, and uniformly mixing the mixture by ultrasonic mixing to obtain a silane coupling agent-modified Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; (4) filling the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material modified by the silane coupling agent obtained in step (3) into the grooves of the fan-ring texture on the inner wall of the sleeve obtained in step (2) by cold spraying technology, and then transferring it to a vacuum sintering furnace for vacuum sintering; (5) After vacuum sintering in step (4), the sleeve is heated to 220-250° C. for vacuum infiltration. After the infiltration is completed, it is slowly cooled to room temperature and then polished to obtain a sleeve with a surface texture filled with Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material.
6. The use according to claim 5, characterized in that: In step (1), the power of the laser engraving machine is 20-30W, the defocus distance is 1.5-2.5mm, and the processing speed is 0.8-1.2 mm / s; in step (2), the phosphating time is 10-15min, and the temperature is 50-80°C; in step (3), the amount of silane coupling agent is 1.8-2.1wt.% of the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material; in step (4), the working gas for cold spraying is helium, the working pressure is 1.5-2.5MPa, the working gas temperature is 180-190°C, the spray angle relative to the geometric section of the inner wall is 77-85°, the vacuum sintering temperature is 150-180°C, and the duration is 80-100min; in step (5), the vacuum infiltration time is 20-40min, and the slow cooling rate is controlled within 10°C / min.
7. The method for preparing the Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material according to claim 1, characterized in that: Ti4AlN3MAX phase ceramic powder 4-11wt.%, SnAgCu powder 84-94wt.% and nano-Al2O3 powder 2-5wt.% are mixed, ball-milled evenly and loaded into a mold, and cold isostatic pressing is used to obtain a Ti4AlN3-nano-Al2O3-SAC solid blank; then, the solid blank is subjected to melt spray granulation technology to prepare a Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material.
8. The preparation method according to claim 7, characterized in that: The specific steps include: 1) According to mass percentage, 4-11wt.% of Ti4AlN3MAX phase ceramic powder, 84-94wt.% of SnAgCu powder and 2-5wt.% of nano-Al2O3 powder are mixed, and after vibrating the mixture, the mixture is put into a vacuum ball mill for ball milling to obtain an initial powder batch of Ti4AlN3-nano-Al2O3-SAC; 2) The Ti4AlN3-nano-Al2O3-SAC initial powder ingredients are uniformly loaded into a mold and filled tightly, water is added as a liquid medium, and then cold isostatic pressing is performed, and after demolding and drying, a Ti4AlN3-nano-Al2O3-SAC solid blank is obtained; 3) Melting the Ti4AlN3-nano-Al2O3-SAC solid blank under vacuum to obtain a melt; atomizing the melt, and then rapidly spraying it into water to cool and solidify, forming a powdery spherical Ti4AlN3-Al2O3 reinforced SAC composite wear-resistant material on the water surface.
9. The preparation method according to claim 8, characterized in that: The titanium aluminum nitrogen MAX phase ceramic, i.e., Ti4AlN3MAX phase ceramic powder, has a particle size of less than 200 meshes; nano-Al2O3 and SnAgCu alloy are both powder raw materials, the particle size of nano-Al2O3 is 100-200nm, and the particle size of SnAgCu alloy is 2-12μm; the SnAgCu alloy consists of Sn 95-97%, Ag2-4%, and Cu 0.1-1% by mass percentage.
10. The preparation method according to claim 8, characterized in that: In step 2), the cold isostatic pressing pressure is 200-300 MPa, and the holding time is 10-20 min; in step 3), the melting temperature is 220-230° C., the atomizing gas pressure is 1-2 MPa, and the diameter of the spherical powder is 8-40 μm.